Tax and the Forgotten Classes: from the Magna Carta to the English Revolution - John Passant (Australasian Accounting, Business and Finance Journal, 2016)
This paper looks at three key early events in English tax history, the 1215 Magna Carta, the Peasants' Revolt of 1381 and the English Revolution from 1640 to 1649. It uses these events to explore the relationship between tax, war, democracy and rebellion. Tax is both an expression of and a cause of class divisions that is can, and does as these events show, spark revolts against the state imposing the taxes. These revolts can be between members of the ruling elite, or between the people outside the ruling elite and that group of rulers both political and economic, or a mixture of both. The aim is to reintroduce class into tax history and show over time the crucial role ordinary people (for example peasants, artisans and workers) play in the history of taxation. Thus the people of London played a role in the successful rebellion of the Barons against the kings' imposition of excessive tax and the establishment of a common counsel of the elite to approve future extractions. This gain became the bedrock for future democratic demands, for example no taxation without representation. Peasants drove the revolt of 1381 against poll taxes but could not make demands that transcended their particular class position although they gave hints of an alternative non-class divided society. In 1629 Ship Money enabled the King to rule without parliamentary approval and this eventually sparked the rebellion and then revolution from 1640 in the context of a society changing from feudal to capitalist relations. In all three cases the actions of the masses of ordinary people are a key to understanding the events and the intertwining of war, tax, democracy and rebellion that becomes evident during this investigation.